Race, racialization, and antiracism in Canada and beyond - Johnson, Geneviève Fuji; Enomoto, Randy (University of Toronto Press, 2007)
Examines expressions of racism in contemporary policy areas, including education, labour, immigration, media, and urban planning. This title argues that, in order to combat racism, various methodological approaches are required, approaches that are reflective of the diversity of the world we seek to understand.